2021
DOI: 10.1371/journal.pone.0254374
|View full text |Cite
|
Sign up to set email alerts
|

Network-based repurposing identifies anti-alarmins as drug candidates to control severe lung inflammation in COVID-19

Abstract: While establishing worldwide collective immunity with anti SARS-CoV-2 vaccines, COVID-19 remains a major health issue with dramatic ensuing economic consequences. In the transition, repurposing existing drugs remains the fastest cost-effective approach to alleviate the burden on health services, most particularly by reducing the incidence of the acute respiratory distress syndrome associated with severe COVID-19. We undertook a computational repurposing approach to identify candidate therapeutic drugs to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 73 publications
(87 reference statements)
0
10
0
Order By: Relevance
“…All of these observations have prompted researchers to develop strategies to modulate proinflammatory cytokine levels, and a possible treatment to reduce the incidence of ARDS in COVID-19 patients has been studied [16,[35][36][37].…”
Section: The Immunementioning
confidence: 99%
“…All of these observations have prompted researchers to develop strategies to modulate proinflammatory cytokine levels, and a possible treatment to reduce the incidence of ARDS in COVID-19 patients has been studied [16,[35][36][37].…”
Section: The Immunementioning
confidence: 99%
“…The targeted inhibition of TSLP could help prevent the damaging sequelae of COVID-19. In support of this suggestion, a recent report suggested that alarmin cytokines such as TSLP are targets of major therapeutic interest in COVID-19, although few clinical trials are being conducted at present to target these during COVID-19 infection [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“… Title Datasets used Repurposed Drugs Evaluation Criteria Tools used Ref. 1 Network medicine framework for identifying drug-repurposing opportunities for COVID-19 13 Datasets, DrugBank, STRING 989 Drugs, 77 Validated in VeroE6 Cells, 76/77 validated in Human Cells Network proximity, network diffusion, Network AI Experimental, Ensembl algorithmic prediction [176] 2 Drug repurposing for COVID-19 using graph neural network and harmonizing multiple evidence CTDbase, STRING, Hetionet, DrugBank 22 drugs and drug combinations Validation with multiple sources, In-vitro screening GSEA, Plotly, Gephi, GNN [178] 3 COVID-19 Multi-Targeted Drug Repurposing Using Few-Shot Learning Chemical Molecules, ZINC, ChEMBL, Loss function and metrics Few-shot learning [179] 4 Machine learning and network medicine approaches for drug repositioning for COVID-19 STRING, ChEMBL, DrugBank In-vitro, In-vivo, clinical trials, and CMAP [180] 5 Using informative features in machine learning based method for COVID-19 drug repurposing STRING, DrugBank, Uniprot 80 % of the predictions were verified Statistical and clinical evidence Enrichment analysis, [182] 6 An integrative drug repositioning framework discovered a potential therapeutic agent targeting COVID-19 Literature, DrugBank, CTD, Uniprot, CMap 41 Drugs wet-lab, Expression profiles of patients and drug perturbation cells, clinical trials data Molecular docking [183] 7 Network-based repurposing identifies anti-alarmins as drug candidates to control severe lung inflammation in COVID-19 Uniprot, STRING, CMap, LINCS, GEO Gene expression profiling, CMap ranking LINCS tools [184] …”
Section: Network Based Studies For Covid-19mentioning
confidence: 99%
“… Title Datasets used Repurposed Drugs Evaluation Criteria Tools used Ref. 1 Designing a Network Proximity-Based Drug Repurposing Strategy for COVID-19 BioGRID Network proximity/ Network Diffusion Cytoscape, VarElect tool [169] 2 Network medicine framework for identifying drug-repurposing opportunities for COVID-19 13 Datasets, DrugBank, STRING 989 Drugs, 77 Validated in VeroE6 Cells, 76/77 validated in Human Cells Network proximity, network diffusion, Network AI Experimental, Ensembl algorithmic prediction [176] 3 Drug repurposing for coronavirus (SARS-CoV-2) based on gene co-expression network analysis DGIDb, gene co-expression, DrugBank 5 Drugs Gene enrichment analysis for Genes and miRNA Node degree and centralities [195] 4 Network-based repurposing identifies anti-alarmins as drug candidates to control severe lung inflammation in COVID-19 Uniprot, STRING, CMap, LINCS, GEO Gene expression profiling CMap ranking [184] 5 Integrative In Silico Investigation Reveals the Host-Virus Interactions in Repurposed Drugs Against SARS-CoV-2 STITCH, KEGG, BioGRID, PubChem, IID, Enrichment analysis, Molecular docking DAVID, GOplot, AutoDock Vina, Cytoscape, Ligplot+ [196] 6 Discovery of Potential Therapeutic Drugs for COVID-19 Through Logistic Matrix Factorization with Kernel Diffusion 4 Drugs 5-fold cross validations, AUC, AUPRs, recall, similarity diffusion Molecular docking [197] 7 HeTDR: Drug repositioning based on heterogeneous networks and text mining Mesh, DrugBank, PubMed 10 Drugs AUPR, AUROC, F1-measure [198] 8 ...…”
Section: Network Based Studies For Covid-19mentioning
confidence: 99%